The perceptions of Islamic bankers, regulators and shari’ah scholars on Islamic microfinance; a case study of Pakistan - Abbas, Kausar; Abdul Razak, Dzuljastri (The Malaysian Current Law Sdn. Bhd. (MCLJ) & International Institute of Advanced Islamic Studies (IAIS), 2013)
This study examines the perceptions of bankers, regulators and Shari‘ah scholars on the issues and challenges concerning the implementation of Islamic microfinance in Pakistan; and whether an appropriate Islamic microfinance instrument can be adopted as an alternative to the conventional model of microfinance for poverty alleviation. The research applied the questionnaire survey methodology where data was collected from five full-fledged Islamic banks of Pakistan. A total of 100 respondents were selected to complete the self- administered questionnaire and the response rate was 50 percent. Three of the sample banks were selected from Islamabad and two banks from Lahore because of the well-established banks in these two cities of Pakistan. The findings are divided into four sections: (1) The function of Islamic microfinance in poverty alleviation; (2) Islamic microfinance’s contribution to the community; (3) Islamic bank’s approach towards Islamic microfinance; and (4) Challenges for Islamic microfinance. It is shown in this study that generally, the Islamic bankers are unanimous that Islamic banks should offer Islamic microfinance and treat it separately from other products. There was general agreement amongst top and middle management that Murabahah, Dimishing musharakah and Ijarah are the most applicable models for Islamic microfinance schemes for the potential micro-entrepreneurs. It is concluded that the findings could provide insights to Islamic banks in diversifying their products to offer Islamic microfinance to the poor. Recommendations are made to have proper guidelines and policies if Islamic microfinance is offered to the poor.